The efficacy of TACE combined sorafenib in advanced stages hepatocellullar carcinoma - Qu, Xu-Dong (BioMed Central, 2012)
BACKGROUND: The long-term survival in hepatocellullar carcinoma (HCC) patients after transarterial chemoembolization (TACE) remains dismal due to local and/or regional recurrence as well as distant metastasis. The efficacy of sorafenib in advanced HCC has been demonstrated and brought great hope. Recently, the use of sorafenib in combination with TACE for BCLC stage B and C HCC patients was recommended. However, data on this dual-modality treatment is little, and its advantage over TACE alone has not been addressed. The present study sought to understand the efficacy of the combination of TACE and sorafenib in the treatment of advanced HCC. METHODS: Between June 2008 and Feb 2011, 45 patients with advanced HCC were enrolled and treated with sorafenib in combination with TACE according to an institutional protocol of the Zhongshan hospital, Fudan University. The control group of 45 other HCC patients with similar characteristics treated with TACE alone in the same period of time in our institute were selected for retrospective comparison of the treatment outcomes especially overall survival time. Adverse reactions induced by sorafenib were observed and recorded. RESULTS: The median overall survival time of the combined treatment group was 27 (95% Confidence Interval: 21.9–32.1) months, and that of TACE alone group was 17 months (95% Confidence Interval: 8.9–25.0) months (P = 0.001). Patients required significantly less frequent TACE for their symptomatic treatment after the initiation of sorafenib therapy. The most common adverse events associated with sorafenib were hand-foot skin reaction, rash and diarrhea. Of CTCAE grade IV or V toxicity was observed. CONCLUSION: TACE combined sorafenib significantly prolonged median overall survival time of patients with advanced HCC.